What is Required of Halal Standards and Halal Certification Systems in the Global Era? - Ohgata, Satomi (Faculty of Islam Nusantara University of Nahdlatul Ulama Indonesia (UNUSIA) Jakarta., 2024)
Over the past 20 years, halal standards promoted by Muslim-majority countries have become increasingly stringent. This movement, which began in Southeast Asia, has extended to the Middle East, and efforts are underway to establish these stringent standards as international norms. Consequently, in Muslim-minority countries like Japan, it has become difficult to manufacture halal products in regular facilities, making it challenging to provide necessary services to Muslim consumers. Additionally, the lack of information regarding changes in alcohol standards poses a problem. International halal standards have also reclassified certain seasonings from non-Muslim regions, previously considered halal by local Muslims, as non-halal. This paper focuses on Indonesia's halal certification standards and system, examines the current state of halal compliance in Japan, and explores the relationship between the two. It aims to discuss the necessary reforms for halal standards and certification systems in the global era.